Environmental knowledge and attitude among students in Sabah - Harun, Rosta; Lim, Kuang Hock; Othman, Fadhilah (IDOSI Publications, 2011)
Environmental awareness among students is highly influenced by their background, knowledge, attitude and sensitivity towards the environment. The objectives of this study are to identify level of knowledge on environmental literacy and attitude towards environmental issues that are occurring in Malaysia presently among students in Sabah, Malaysia. Multi-stage stratified sampling was used to select the samples. Data was collected using self-administered questionnaire which was developed by expert panel which consisted of lecturers and teachers through two sessions of focus group discussions (FGD). The items developed for the questionnaires took into consideration the environmental problems which have existed locally as well as cultural sensitivities of local community. Pilot test among 50 form four secondary school students show moderate level of internal l consistency of knowledge (Cronbach Alpha -0.68) and attitude (Cronbach alpha 0.72) domains. 1106 (95%) of 1200 sample responded the study. The result show that in general, students in Sabah particularly from Form 4 level have high level of environmental knowledge except for several items which measure the current environmental issues in Malaysia such as Carbon dioxide and climate change. Their attitudes are influenced by the level of knowledge that they have concerning the environment.